2013
DOI: 10.1177/0333102413512033
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of medication-overuse headache in population-based studies and their implications on prevalence estimates: A systematic review

Abstract: There are limits to comparing prevalence of MOH across studies and over time. The wide range of reported prevalence might not only be due to changing criteria, but also the diversity of countries now publishing data. The criterion "headache occurring on ≥15 days per month" with concurrent medication overuse can be applied in population-based studies. However, the new requirement that a respondent must have "a preexisting headache disorder" has not been previously validated. Exclusion of other headache diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 101 publications
3
105
0
15
Order By: Relevance
“…TTH, despite being the second most prevalent disorder in the world (behind dental caries) [7], adds much less to population disability estimates because a low disability weight of 0.036 (on a scale of 0–1) is accorded to the headache of TTH compared with 0.434 for the ictal state of migraine [17]. MOH is recognised as far more disabling at an individual level but, with its prevalence still very poorly estimated in many regions [18, 19], it stays ranked as 18 th cause of YLDs in GBD 2015 [15]. …”
Section: How Much Headache Is There In the World?mentioning
confidence: 99%
“…TTH, despite being the second most prevalent disorder in the world (behind dental caries) [7], adds much less to population disability estimates because a low disability weight of 0.036 (on a scale of 0–1) is accorded to the headache of TTH compared with 0.434 for the ictal state of migraine [17]. MOH is recognised as far more disabling at an individual level but, with its prevalence still very poorly estimated in many regions [18, 19], it stays ranked as 18 th cause of YLDs in GBD 2015 [15]. …”
Section: How Much Headache Is There In the World?mentioning
confidence: 99%
“…However, a recent review concludes that this varies in different parts of the world depending on the definitions used. The review reported a wide range of prevalence, ie, 0.5%–7.2% 45. The incidence of MOH was 0.72 per 1,000 person-years in a large prospective cohort study from Norway 46…”
Section: Epidemiologymentioning
confidence: 99%
“…MOH, highly burdensome at individual level [2], may be seen in almost all cases as a complication of either migraine or TTH [6]. It has yet to be recognized in global surveys such as GBD [8-10] because of lack of epidemiological data, itself in part due to difficulties over case definition and ascertainment in population surveys [11,12]. …”
Section: Introductionmentioning
confidence: 99%